2011
DOI: 10.1002/hpm.1038
|View full text |Cite
|
Sign up to set email alerts
|

Setting health insurance remuneration rates of private providers in Kenya: the role of costing, challenges and implications

Abstract: Successful health financing depends on prudent design of resource collection, pooling and purchasing. One of the critical purchasing design issues is the provider payment mechanism and the remuneration rates, which need to set appropriate incentives to health providers. In order to set remuneration rates, cost information is required, but this is not known in many developing countries. This paper illuminates the role of costing and the challenges of resetting health insurance remuneration rates for private hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…NHIF members can access inpatient services at government facilities, as well as private for- or non-profit facilities that are accredited by NHIF [ 39 ]. The creation of the outpatient scheme has for the first time opened NHIF accreditation possibilities for facilities that do not offer inpatient services.…”
Section: Introductionmentioning
confidence: 99%
“…NHIF members can access inpatient services at government facilities, as well as private for- or non-profit facilities that are accredited by NHIF [ 39 ]. The creation of the outpatient scheme has for the first time opened NHIF accreditation possibilities for facilities that do not offer inpatient services.…”
Section: Introductionmentioning
confidence: 99%
“…Mackintosh et al [11] examined the public-private healthcare provider mix by looking at three dimensions of public contract models; the rationale behind the purchasing arrangements; issues occurring as a result of purchasing arrangements; and the best means for public purchasers to buy private healthcare services under public contract systems [8,9].…”
Section: Methodsmentioning
confidence: 99%
“…In such cases, it is difficult to assess the inefficiencies associated with using higher payment rates for private providers. In fact, in many countries, the use of evidencebased or full costing approaches to determine payment rates is not clearly documented [9]. Use of higher payment rates for private healthcare providers may also cause cost pressure on healthcare supply across the system, resulting in an overall increase in healthcare expenditure in a country [15].…”
Section: Efficiency Equity and Quality Implications Of Payment Rates And Payment Methodsmentioning
confidence: 99%
“…Our study identified a number of opportunities and strengths in relation to the viability of a cost accounting system in Kenya – in particular, durable political commitment to digitalization in healthcare, a broad and expanding HMIS infrastructure, as well as a recognized interest from policy makers and practitioners at all levels for relevant unit cost data. In addition, a number of control initiatives established by the MoH, such as performance management, activity-based funding for maternity services, and risk adjusted payment mechanisms for providers, have been shown in the literature to stimulate the establishment and growth of cost accounting infrastructure ( 5 , 9 , 44 ).…”
Section: Discussionmentioning
confidence: 99%